Pemanfaatan Limbah Kulit Pisang Kepok (Musa paradisiaca) Sebagai Pakan Alternatif Ayam Pedaging (Gallus gallus) di Peternakan Ayam Rakyat Desa Labuhan Ratu VII Kecamatan Lampung Timur - Rohmatul Anwar; Diah Reni Asih (Fakultas Peternakan Universitas Halu Oleo, 2023)
Chicken meat is a source of animal food which contains quite high nutrition in the form of protein and energy. This study aims to determine the utilization of kepok banana peels on the growth of broilers. This research was conducted for 2 months, including the preparation of cages until harvest with 1 day old broilers (DOC). The method used in this study was a completely randomized design (CRD) with 5 treatments and 2 repetitions with concentrations of 0% (control), 25%, 50%, 75% and 100% banana peels. As well as analysis using Analysis of Variance (ANAVA), if there is a difference between the treatments, it can be continued with the LSD test (Lessest Significant Difference) with a 95% confidence level. From the results of the research that has been done, the results show that the best broiler body weight gain is 0% banana peel and the lowest is 100% banana peel. The main factor causing the low death of broilers in the 100% banana peel treatment was due to the high C/N content in the banana peel. The conclusion that can be drawn from this study is that the higher the concentration of feed given to broiler feed the lower the average growth of broilers. As well as processed feed made from kepok banana peels at a concentration of 25% -75% all of which can be consumed by broilers to gain weight in broilers because the results are not significantly different.